Analisa Sikap Terhadap Perilaku Pengusaha UKM Pada Pelaksanaan Kredit Program Kemitraan BNI di Sentra Kredit Kecil Cabang Bogor - Hendri Utami; Illah Sailah; Sri Hartoyo (Institut Pertanian Bogor, 2009)
The objectives of the research are to analyze some factors considered by a small enterprises to access banking facility, to study the influence of the attitude toward the behavior of small and medium enterprises (SME’s) in Kredit Program Kemitraan BNI, to analyze the product image of Kredit Program Kemitraan BNI from the point of view of a customer and a businessman, to determine some market segmentation strategies for Kredit Program Kemitraan BNI. The result of research showed that the factor influenced businessman in making relationship with banking were as follows: time effectiveness, privacy, accessibility, low interest rate, transaction, the safety of the money, service excellent and business consultation and accessibility easiness. The research results showed that from 100 respondents of SME’s, 58 of them responded with very positively, 21 of them with positively, 18 of them neutral and 3 of them responded negatively. However, based on product image analysis, Kredit Program Kemitraan BNI did not meet BNI’s expectation. The implementation of market segmentation strategies expected by BNI, concerning the product is by product focus, dealt with price is by keeping low interest rate, and regarding the distribution is by looking for good location, deregulation and procedure, and regarding the promotion is by advertising.